Good Practice with Vulnerable Adults - Pritchard, Jacki (London : Jessica Kingsley, 2001)
This volume addresses key problems and dilemmas in working to protect vulnerable adults - such as the elderly or those with physical disabiities - from abuse, and to support those who have already experienced abuse or neglect.
Includes bibliographical references and index.
Keywords: Social service; Society